Defining power and agency in gender relations in El Salvador: Consequences for intimate partner violence and women’s mental health. - Navarro-Mantas, Laura; De Lemus, Soledad; García-Sánchez, Efrain; McGill, Lucy; Hansen, Nina; López-Megías, Jesús (Frontiers, 2022)
Intimate partner violence (IPV) affects thousands of women around the world and is prevalent in the Global South. Unequal social structures perpetuate hierarchies and maintain women’s vulnerability to violence. Difficulties women face in accessing education, economic resources, and employment diminish their power in intimate relationships, increasing the likelihood of IPV. These factors can also have a significant effect on women’s mental health. However, some studies show that economic empowerment does not necessarily translate into greater agency for women if they cannot use the resources they earn to pursue whatever goals or values they regard as important in life. Agency is women’s ability to identify their life goals and act upon them through critical evaluation (intrinsic agency) and autonomous decision-making (instrumental agency). In this article, we aim to analyze the relationship between women’s power (educational and economic) and agency and their influence on intimate partner violence and on women’s mental health in the context of El Salvador. Currently, El Salvador has one of the highest percentages of femicide worldwide. We used data from the first national survey on violence against women in El Salvador to determine empowerment indicators and investigated their influence on intimate partner violence and women’s mental health. Results from a representative sample of 1,274 women aged between 15 and 64 years old and, using a structural equation modeling revealed that education was a protective factor against IPV, but economic power appeared to put women at greater risk of IPV. Education was positively related to both intrinsic and instrumental agency, but only instrumental agency was negatively associated with the likelihood of being a victim of IPV.
Keywords: Violencia de género; Violencia familiar; Salud mental; Violence against women; Intimate partner violence; Mental health; Agency; Global South; Power